2018
DOI: 10.3390/toxins10050201
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Apoptosis in HepaRG Cell Line Induced by Polyphyllin VI via the Fas Death Pathway and Mitochondrial-Dependent Pathway

Abstract: Polyphyllin VI, which is an active saponin, is mainly isolated from traditional medicinal plant Paris polyphylla, which causes liver damage in rats. In the present study, we aimed to explore the potential cytotoxicity of polyphyllin VI on the growth of HepaRG cells and to determine the molecular mechanism. The results revealed that polyphyllin VI changed cell morphology and induced apoptosis in HepaRG cells. Flow cytometric assay displayed that polyphyllin VI promoted the generation of reactive oxygen species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…For example, Teng et al 6 demonstrated that PPVI could suppress the proliferation of non-small-cell lung cancer, while in hepatocellular carcinoma, it was found to induce apoptosis via the Fas death pathway. 7 However, the effect of PPVI on glioma remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Teng et al 6 demonstrated that PPVI could suppress the proliferation of non-small-cell lung cancer, while in hepatocellular carcinoma, it was found to induce apoptosis via the Fas death pathway. 7 However, the effect of PPVI on glioma remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al found that polyphyllin VII can regulate the expression of Bcl-2 and Bax, cause a decrease in mitochondrial membrane potential (MMP), and induce apoptosis in human erythroleukemia cell line K562 ( 9 ). Liu et al found in the study of the hepatocellular carcinoma HepaRG that polyphyllin VII can increase intracellular ROS production, decrease MMP, and accompany activation of the caspase pathway and the release of cytochrome c from the cytoplasm to induce mitochondrial apoptosis ( 10 ). It is suggested that polyphyllin VII may cause mitochondrial dysfunction of tumor cells and induce apoptosis, although the specific mechanism of regulating mitochondrial function is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…A lower MMP is often followed by the release of cyto-c from the mitochondria to the cytoplasm (17), which mediates apoptosis with the participation of Bcl-2 family proteins (18). Bcl-2 and Bcl-xL are generally considered to play a role in preventing apoptosis and cell death caused by various stressors (19).…”
Section: Discussionmentioning
confidence: 99%